Atmospheric, radiative, and hydrologic effects of future land use and land cover changes: A global and multimodel climate picture. Issue 10 (17th May 2017) - Quesada, Benjamin; Arneth, Almut; de Noblet‐Ducoudré, Nathalie
Abstract: Land use and land cover changes (LULCC) modulate land surface energy, heat, moisture, and momentum fluxes. Using simulations performed with and without LULCC for five earth system models, averaged over the 2071–2100 period, we quantify the biophysical effects in response to a future realistic LULCC scenario (Representative Concentration Pathway RCP8.5) on 15 climate variables (i.e., atmospheric, radiative, wind, hydrologic variables, and heat fluxes). We find that climate models are able to simulate some robust and strong climate perturbations in response to LULCC. In tropical regions with substantial LULCC, significantly higher skin temperatures, less precipitation and soil moisture, less evaporation and clouds, more incoming radiation and stronger winds, more anticyclonic conditions and subsidence, are simulated in response to future LULCC. In midlatitude and high latitude, LULCC result in autumn cooling and higher tropospheric pressures, while East Asia is drier, warmer, with higher sensible heat flux and lower evaporation. The tropical wind strengthening and weakening of the hydrological cycle are comparable in magnitude to their future regional changes induced by greenhouse gases under RCP8.5, which make LULCC an indispensable forcing to take into account in future climatic assessments. Finally, our study reveals significant indirect atmospheric processes triggered by LULCC, implying substantial changes in incoming radiation, which dominate climatic responses over the direct effects, particularly in boreal regions. Plain Language Summary: Trees affect climate not only by modulating greenhouse gases sequestration but also by regulating the exchange of energy, heat, water, and momentum with the atmosphere. However, few studies quantified, in a consistent way, all the latter perturbations for a realistic deforestation scenario or with several models. Analyzing five earth system models, for a common future business‐as‐usual land use and land cover changes (LULCC) scenario, we show that significant atmospheric, radiative, and hydrologic changes are robustly simulated. Among others, the weakened hydrological cycle and the wind strengthening due to tropical deforestation are comparable in magnitude to the projected changes induced by greenhouse gases. Our investigation also reveals significant indirect atmospheric processes triggered by LULCC, implying substantial changes in incoming radiation, which dominate climatic responses over the direct effects (albedo, evapotranspiration, or roughness changes), particularly in boreal regions. In consequence, LULCC are a critical forcing that needs to be taken into account for future climatic assessments. Key Points: A large panel of future biophysical effects of land use and land cover changes (LULCC) is assessed and quantified in a multimodel framework Future LULCC weaken the hydrological cycle and reveal a positive tropical soil‐moisture/precipitation feedback after deforestation Indirect atmospheric feedback can dominate over direct effects to explain simulated climatic changes